Cholera in the World - Walaa Shakir Mahmood (International Journal of Medical Toxicology and Legal Medicine, 2024)
Cholera is a contagious, sudden bacterial illness caused by Vibrio Cholerae. The main clinical symptom of the illness is watery diarrhea. Globally, it is believed to account for nearly 4 million cases each year. This digestive infection is marked by significant fluid loss and electrolyte imbalances that can lead to hypovolemic shock and ultimately death. Cholera continues to pose a worldwide danger and is a significant measure of societal progress. Cholera disease has a greater impact on low-income nations compared to those with middle or high income. These findings reinforce the statement that "cholera is a sickness associated with poverty." The reappearance of cholera is creating unprecedented difficulties in the Eastern Mediterranean Region.(EMR), where it is regarded as endemic in nine member countries. The possibility of a cholera epidemicWe examine the local patterns of cholera,regional challenges and burden, emphasizing initiatives by the World Health Organization (WHO) inthe area that may be beneficial in stopping and managing the illness in alike situations.In spite of considerable advancements in cholera management globally, the illness remains asignificant public health issue throughout the region, where it represents both an emerging and reemerging danger. Frequent cholera outbreaks signify inadequate water and sanitation conditions along with fragile health systems, facilitating the transmission and propagation of the disease.